Prehospital emergency management of avulsed permanent teeth: Knowledge and attitude of schoolteachers - Harkiran Kaur; Supreet Kaur; Hargundeep Kaur (Wolters Kluwer Medknow Publications, 2012)
Context: Tooth avulsion is one of the most serious dental emergencies in children. Often these injuries occur in school and, therefore, the knowledge of schoolteachers regarding the appropriate measures to be taken immediately after tooth avulsion is crucial to good prognosis. Aims: The purpose of the present study was to evaluate schoolteachers' knowledge and attitudes regarding immediate management of avulsed teeth in children. Materials and Methods: A total of 177 teachers from seven schools of Garhshankar town, Hoshiarpur District, Punjab, India, formed the sample of the study. A self-administered questionnaire consisting of 16 questions was used to assess the knowledge and attitudes of schoolteachers about tooth avulsion and its management. Statistical Analysis: The chi-square test and one-way analysis of variance (ANOVA) were used for analysis. Pair-wise comparison was done using Tukey's honestly significant difference (HSD) test. P≤0.05 was considered to be statistically significant. Results: Markedly low knowledge levels were noted among the schoolteachers. The mean knowledge score was 5 (of a maximum possible score of 10). Only 0.6% of the teachers answered correctly that they would use milk as a transport medium. The number of correct responses was not affected by previous experience with tooth avulsion, sex, educational level, teaching experience, or teacher training. Overall, 85.9% of teachers showed a positive attitude towards this campaign. Conclusions: Knowledge regarding emergency management of dental trauma is poor amongst schoolteachers. Therefore, we suggest that orientation to management of avulsed tooth be part of the teacher training education.